2008
DOI: 10.1149/1.3013289
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Investigations of the Fries Rearrangement in Ionic Liquids

Abstract: The Fries rearrangement of phenyl benzoate has been studied in the AlCl 3 : 1-butyl-1-methylpyrrolidinium chloride buffered neutral ionic liquid, giving results similar to those found in the analogous 1-ethyl-3-methylimidazolium chloride system. In the former system, it is possible to observe the reduction of sodium ion, allowing assessment of the buffer level in the system. Further work involves the Fries rearrangement of phenyl benzoate in 1-butyl-1-methylpyrrolidinium triflate ionic liquid. In contrast to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The observation of reduction processes for both protons and protonated phenyl benzoate is puzzling at this point; however, a rapid equilibrium between these two species may explain this result. Previous work (10) has shown that the addition of triflic acid to phenyl benzoate in the 1-butyl-1-methylpyrrolidinium triflate ( BMPY T f O ) ionic liquid does not result in a potential shift for the phenyl benzoate reduction process. This finding was interpreted as a consequence of the influence of the conjugate base of triflic acid ( triflate anion ) in the ionic liquid, effectively making the triflic acid less acidic in this medium than in EMI BF 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation of reduction processes for both protons and protonated phenyl benzoate is puzzling at this point; however, a rapid equilibrium between these two species may explain this result. Previous work (10) has shown that the addition of triflic acid to phenyl benzoate in the 1-butyl-1-methylpyrrolidinium triflate ( BMPY T f O ) ionic liquid does not result in a potential shift for the phenyl benzoate reduction process. This finding was interpreted as a consequence of the influence of the conjugate base of triflic acid ( triflate anion ) in the ionic liquid, effectively making the triflic acid less acidic in this medium than in EMI BF 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent work in this and other laboratories has involved the study of the Fries rearrangement in ionic liquid systems (3)(4)(5). The reaction has been successfully carried out in the AlCl 3 : 1-ethyl-3-methylimidazolium chloride ( EMIC ) chloroaluminate system (4); however, use of ionic liquids such as EMI BF 4 and BMPY T f O, to which Lewis acids were added, has met with more limited success (5,10). The present work investigates the use of proton acids ( triflic acid, p-toluenesulfonic acid ) in the Fries rearrangement of phenyl benzoate in EMI BF 4 ionic liquid.…”
Section: Introductionmentioning
confidence: 99%
“…In an ongoing study of the Fries rearrangement, in which phenyl benzoate produces hydroxybenzophenone products, the electrochemical behavior of various Lewis acids ( BF 3 , AlCl 3 , Hf(TfO) 4 ) has been investigated in both ionic liquids (1,2) and acetonitrile (3). The present work begins an effort to understand the formation of Lewis acid complexes with carbonyl compounds in a broader sense, specifically involving aromatic ketones.…”
Section: Introductionmentioning
confidence: 99%
“…Anhydrous nickel was dried in vacuo for 24 hours. 1-ethyl-3-methylimidizolium chloride (EMIC) was prepared by reaction of 1methylimidazole and 1-chloroethane as described previously (21), and aluminum chloride (Fluka) was purified by closed-tube distillation over aluminum wire (22). The preparation of the samples was done in a dry box under a N 2 atmosphere where the oxygen and water content were kept below 1 ppm.…”
Section: Methodsmentioning
confidence: 99%